The Linkage Between Financial Literacy and Digital Entrepreneurial Intention: The Mediation and Moderation Role of Entrepreneurship Education and Social Media - Najjuah Najjuah; Agus Wibowo; Aditya Pratama (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2024)
This research aims to examine the influence of financial literacy and digital entrepreneurial intentions, as well as investigate the mediating role of entrepreneurship education and the moderating role of social media. This research used primary data obtained from 154 students in Jakarta of Indonesia, through a self-administered survey with online questionnaires. The retrieved data were further analyzed using partial least square structural equation modeling (PLS-SEM) with Smart-PLS 4.0. The research results indicate that there is a positive and significant influence of financial literacy and entrepreneurship education on digital entrepreneurial intentions among students. In addition, entrepreneurship education has been confirmed to mediate the linkage between financial literacy and digital entrepreneurial intentions. Meanwhile, social media failed in mediating the influence of financial literacy and entrepreneurship education on digital entrepreneurial intentions. This proves that digital literacy is essential for almost every aspect of education, allowing potential entrepreneurs to take advantage of technological developments and offering valuable insights for designing targeted interventions and policies to foster a more robust digital entrepreneurial ecosystem.